The Dynamic of Shiva-Sisya (Patron Client) Relationships Within Hindu’s Practice in Denpasar City - Anom Kumbara, AA. Ngurah; Kartika Dewi, AA. Sagung (Udayana Journal of Social Sciences and Humanities; Vol 1 No 1 (2017): UJoSSH, Feburary 2017, 2017)
Modernization and globalization have spread the ideology of capitalism and materialistic rationalism throughout the world. It has created transformation not only in the socio-cultural and economic aspects, but also in religion practice. One of the Hindu’s practice phenomenon that prevails nowadays in Denpasar is a certain dynastic lawsuit against shiva-sisya relationship (patron-client), which became a tradition in Hindu’s practice in Bali.The purpose of this study is to understand and explain the background of the shifting in shiva-sisya (patron client) relationship and the implications of this shift within Hindu’s practice or religiosity in Denpasar city. To answer the purpose of this study cultural studies approach was used with qualitative analysis. Techniques for collecting data were through in-depth interviews, observations and analysis of the related documents. This study used theories: Patron-Client by James Scott, Structuration by Giddens and Modernization/social change of Marx. Based on the analysis of the collected data, this study has found that the underlying shift in the relationship of shiva-sisya (patron-client) within Hindu’s practice in Denpasar city was the appearance of the religious power decentralization, the strengthening of the market ideology within Hindu’s practice and structured social relations. The implications of that shift, which happen to be the religion privacy and the emergence of Hindu’s internal friction in religious practice in Denpasar city.